Ocular Complications in Cutaneous Lupus Erythematosus: A Systematic Review with a Meta-Analysis of Reported Cases - L. Arrico; A. Abbouda; I. Abicca; R. Malagola (Journal of Ophthalmology)
Ocular complications associated with cutaneous lupus erythematosus (CLE) are less studied compared with those ones associated with systemic lupus erythematosus (SLE). The main ocular sites involved in patients affected by discoid lupus erythematosus (DLE) are eyelids followed by orbit and periorbit, the least being cornea. The most common complications are blepharitis usually affecting the lower lid and associated with some type of lid lesion such as plaque or erythematosus patches and madarosis. Few cases with LE profundus (LEP) and ocular complications are reported, but they are associated with orbital inflammatory syndrome and severe complications. The main treatment prescribed is hydroxychloroquine with a dose of 200 mg twice a day for 6 to 8 weeks. Corticosteroids are also used. Intervals between the correct diagnosis and the beginning of the ocular symptoms are commonly delayed. Ophthalmologist should be aware of the ocular manifestation of this autoimmune disease.